BEHIND THE SCENES OF ANONYMOUS: POWER MECHANISMS AND ONLINE PROSTITUTION PRACTICES ON MICHAT - Fatimah, Syarifah; Ronda, Mirza; Napitupulu, Frengki (Bajang Institute, 2025)
The development of digital technology has created new interaction spaces that enable online prostitution, one of which is through the MiChat application. The anonymity and people nearby features make it easier for users to interact without clear identities, creating a loophole for covert sexual transactions. This research uses a critical paradigm with a qualitative approach through interviews, digital observation, and document analysis to understand how anonymity operates as a mechanism of power. The results show that coded language such as